Price formation within Egypt's wheat tender market: Implications for Black Sea exporters - Maximilian Heigermoser; Linde Götz; Miranda Svanidze (Agricultural Economics, 2021)
Black Sea wheat exporters, led by Russia, dominate Egypt's wheat imports via a tender system. The tenders are managed by the GASC and their outcomes are communicated worldwide by financial news agencies. Building on a transaction-specific dataset on GASC tenders (2011 - 2019), results of our cointegration analysis find wheat export markets of Russia, France and the USA highly integrated with the GASC tender price. Estimates from the multivariate VECM indicate strong price interdependencies between the GASC tender price and Russian and French export prices, indicating fierce competition in the GASC tender market. Despite the high market share of wheat exporters in the Black Sea region and Russia in particular, tests on weak exogeneity suggest a leading role of the French wheat export price. We further find that leadership of US wheat prices is weak in the GASC tender market.
Keywords: Q11; Q13; Q17; 630; Black Sea region; multivariate cointegration; spatial market integration; wheat